2012
DOI: 10.1177/1032373212443225
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for a nation’s beginnings: Challenges arising from the formation of the Dominion of Canada

Abstract: This article presents an historical study of the accounting issues and challenges arising from the creation of a new nation, the Dominion of Canada. We document the issues associated with combining the accounting of three separate pre-confederation political entities and describe how the first accounting system for Canada was put in place. The study identifies significant challenges resulting from a lack of formal accounting policies, the settling of accounts between the provinces and the new dominion, account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In a prior article (Baker and Rennie, 2012), we reported that the first public accounts of the Dominion of Canada were formulated in much the same fashion as had been the public accounts of one of the dominion's three predecessor entities, the Province of Canada, a province whose existence was terminated with the creation of the Dominion of Canada -that is, we observed institutional persistence. Prior historical studies note the importance of the Durham Report and the brief work of Lord Sydenham in shaping the structure of the public service of the Province of Canada, the largest province at confederation (Careless, 1967;Hodgetts, 1956).…”
Section: Potential Influential Forces For Accounting Practices Of Thementioning
confidence: 75%
“…In a prior article (Baker and Rennie, 2012), we reported that the first public accounts of the Dominion of Canada were formulated in much the same fashion as had been the public accounts of one of the dominion's three predecessor entities, the Province of Canada, a province whose existence was terminated with the creation of the Dominion of Canada -that is, we observed institutional persistence. Prior historical studies note the importance of the Durham Report and the brief work of Lord Sydenham in shaping the structure of the public service of the Province of Canada, the largest province at confederation (Careless, 1967;Hodgetts, 1956).…”
Section: Potential Influential Forces For Accounting Practices Of Thementioning
confidence: 75%
“…As the name suggests, a primary function of the Board was to audit the financial information produced by the government. The Board was also responsible for the development of accounting policies (Baker and Rennie, 2012). The 1867 statute also indicates that it was the duty of the Board of Audit “to prepare and submit to the Minister of Finance the Public Accounts to be annually laid before Parliament” (Statutes of Canada, 1867: paragraph 27).…”
Section: Resultsmentioning
confidence: 99%
“…We contribute to the literature that is concerned with the history of accounting standard setting generally and, in particular, the literature that addresses the history of government accounting by adding to previous contributions, including Baker and Rennie (2006, 2011, 2012, 2013, 2017), Buhr (2012), Carpenter and Feroz (2001), Chan (1985, 2003) Chua and Sinclair (1994), Ellwood (2002), Jones (1992), Lin (1993), Lin et al (1993), and Pallot (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies offer a connection between governmental programmes and the accounting information as a technology of government (e.g. Baker and Rennie, 2012;Colquhoun and Parker, 2012;Gomes et al, 2014;Lai et al, 2012) and have presented accounting as a useful instrument in managing populations (Sánchez-Matamoros et al 2016) through the concept of action at a distance (e.g. Neu, 2000aNeu, , 2000bSargiacomo, 2008Sargiacomo, , 2009.…”
Section: Governmentalitymentioning
confidence: 99%